Habitat diversity, Morphological and systematic analysis of multipotential species of Aloe barbadensis Mill. (Liliaceae) from the Southern Western Ghats of Tamil Nadu, India - Thomas, Binu; M, Parthipan; A, Rajendran (Journal of Research in Biology, 2011)
The present paper highlights the habitat variability, morphological features, systematic analysis and multi potentiality of Aloe barbadensis Mill. were collected from Nilgiri district of Southern Western Ghats of Tamil Nadu, India. The epiphytic nature of Aloe barbadensis Mill. is quite interesting than other habitats